Frequency of Complications of Transforaminal Lumbar Interbody Fusion (TLIF): A Single Center Experience. (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To determine the frequency of complications of Transforaminal Lumbar Interbody Fusion (TLIF) in tertiary care hospital.Methods: This retrospective Cohort study was conducted in Department of Orthopedics and spine surgery Hayat Abad medical complex Peshawar. All patients who underwent Transforaminal Lumbar Interbody Fusion (TLIF) for various indications fulfilling the inclusion criteria and operated in time period extending from 2nd January 2012 and 3rd Jan 2020 were included in this study. A thorough evaluation of the patients records were done and frequency of post operative complications were noted.Results: Based upon our inclusion criteria the medical records of 208 patients were examined. Male patients were 50(24%) and female 158 (76%).The mean age was 45±7(range 20 to 74 years).The overall complication rate was 33.6%(n=70).Dural tear was documented in 9(4.3%) patients, 16(7.6%) had postoperative ileus, wound infection in 14(6.7%), radiculopathy in 12(5.7%),motor weakness in 1(0.4% ), 6 (2.8%) had pseudoarthrosis and 12(5.7%) patients had implants related complications. The re surgery rate was 6.2%(n=13)Conclusion: Transforaminal Lumbar Interbody Fusion (TLIF) is a reliable surgical procedure to achieve fusion in a variety of clinical conditions. The complication rate is variable. Careful patient selection, preoperative planning and meticulous intra-operative execution can avoid these complications.